1998
DOI: 10.1523/jneurosci.18-11-04042.1998
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of PC12 Cell Death byN-Acetylcysteine Requires Activation of the Ras Pathway

Abstract: We have shown that N-acetylcysteine (NAC) promotes survival of sympathetic neurons and pheochromocytoma (PC12) cells in the absence of trophic factors. This action of NAC was not related to its antioxidant properties or ability to increase intracellular glutathione levels but was instead dependent on ongoing transcription and seemed attributable to the action of NAC as a reducing agent. Here, we investigate the mechanism by which NAC promotes neuronal survival. We show that NAC activates the Ras-extracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(100 citation statements)
references
References 61 publications
5
95
0
Order By: Relevance
“…7A). Previous studies have demonstrated that the anti-apoptotic effects of NAC in PC12 cells are not due to its antioxidant capacity (60) but are instead dependent on new transcription and the activation of the Ras-ERK signaling pathway (61). Given our data with inhibitors of oxidative stress, we feel that NAC prevents BH 4 -induced DNA fragmentation by a mechanism that does not involve its antioxidant potential.…”
Section: Effect Of N-acetylcysteine or Inhibition Of Cyclin-dependentmentioning
confidence: 53%
“…7A). Previous studies have demonstrated that the anti-apoptotic effects of NAC in PC12 cells are not due to its antioxidant capacity (60) but are instead dependent on new transcription and the activation of the Ras-ERK signaling pathway (61). Given our data with inhibitors of oxidative stress, we feel that NAC prevents BH 4 -induced DNA fragmentation by a mechanism that does not involve its antioxidant potential.…”
Section: Effect Of N-acetylcysteine or Inhibition Of Cyclin-dependentmentioning
confidence: 53%
“…In PC-12 cells, ERK is mainly activated by growth factors and has been shown to be associated with cell proliferation, differentiation, and promotion of cell survival (13,16,58,59). H 2 O 2 increased the mRNA expression of the ERKdependent genes egr1, c-jun, c-fos, and mkp1.…”
Section: Discussionmentioning
confidence: 99%
“…The MAP kinases ERK1 and ERK2 (p44 and p42) are known to play a pivotal role in signaling events in the brain where they are involved in neuronal plasticity (11), neuronal survival (12), and processing the amyloid precursor protein (13,14). They play a crucial role in learning and memory, including long term potentiation (15,16) and long term spatial memory (17).…”
Section: Muscarinic Acetylcholine Receptors (Machr)mentioning
confidence: 99%